The reality of the islamic channels in the Arab world - Ali Mahmud Al-Omari; Siti Rugayah Hj. Tibek (Institut Kajian Rantau Asia Barat, 2011)
The new electronic reality imposes its imprint on the world, particularly regarding the media which filled the sky with tens of satellites. As the Arab World is a part of this globe, it has followed the same road as the other countries did. Consequently, it has established hundreds of channels. The first Arabic Islamic channel, Iqra’, was founded at the end of the past century. Then, the other Islamic channels were established one after another to reach more than eighty channels, beaming their programmes via two Arabic satellites: "Arabsat" and "Nilesat". This research is an attempt to analyze the reality of these Islamic channels through surveying three significant issues in any media activity: Women appearing in the Islamic channels, Amusement and Financial funding. The researchers used the inductive approach and the data obtained were analysed to identify the reality of the Islamic channels. Woman should not only be the ornament on the TV screen. They also should obey the juristic of syara’. To immortalize the Islamic channel on the TV screen, they must show a programme that not only commercially based, but should have a permanent source for example from waqaf, in order to allow these channels to implement Islamic programme and produce an interactive entertaining programme with a good message